CO2 emissions of peat soils in agricultural use: calculation and prevention - Van den Akker, J. J. H.; Hendriks, R. F. A.; Pleijter, M. (Agrociencia Uruguay, 2012)
About 9% of the area of the Netherlands is covered by peat soils (about 290,000 ha), mainly drained and in use for dairy farming (about 223,000 ha). Decomposition (oxidation) of peat soils used in dairy farming causes subsidence rates of 12 mm.y-1 The objective of the research was to develop a method to calculate from subsidence the CO2 emissions of peat soils in agricultural use and to test the possibilities of submerged drains to raise groundwater levels and diminish subsidence and CO2 emissions. One mm subsidence by oxidation equals a CO2 emission of about 2.3 tons of CO2 per year per hectare. We calculated that about 3% of the annual anthropological CO2 emission in the Netherlands can be accounted to the oxidation of peat soils. This is about 4.2 Mton CO2 per year. In dry summers the groundwater level lowers well below ditchwater levels, exposing easily biological degradable peat to oxidation. Raising groundwater levels up to ditchwater levels by subsurface irrigation by submerged drains with a spacing from drain to drain of 4 to 6 meters is tested as a possibility to reduce subsidence and CO2 emissions. The experiments started in 2003. Subsidence and so CO2 emissions proved to be reduced by more than 80%. A disadvantage of the use of submerged irrigation might be the increased water usage. Model calculations showed that the amount of inlet water increased on average up to 30%, however, intelligent water management can be a possibility to reduce the extra water usage to about 5%. The modeled reduction in subsidence (and so the CO2 emission) was about 40% of the subsidence in the situation without submerged drains. We concluded that the use of submerged drains can reduce subsidence and CO2 emissions with at least 50%.